The Ethical Poetic of the Later Middle Ages : A decorum of convenient distinction - Allen, Judson Boyce, 1932-1985 (Book collections on Project MUSE., 1982)
This study of the definition of literature in the late medieval period is based on manuals of writing and on literary commentary and glosses. It defines a method of reading which may now profitably explain medieval texts, and identifies new primary medieval evidence which may ground and guide new reading. Allen chooses texts whose commentary tradition provides the greatest opportunity for completeness. The most important of these is Ovid's Metamorphoses. Medieval readings of Ovid bring into focus a number of major literary questions--the problems of fable and fiction, of unity imposed by miscellany poetry, of allegorical commentary, and of Christian use of pagan culture--all in connection with text which furnished medieval authors with more stories than any other single source except possibly the Bible. Allen also studies commentaries on the Consolation of Philosophy of Boethius, the Thebaid of Statius, the De nuptiis of Martianus Capella, the medieval Christian hymn-book, and the Poetria nova of Geoffrey of Vinsauf. Together these texts represent the range of medieval literature--a literature which, Allen concludes, was taken as direct ethical discourse, logically conducted and artfully organized within a system of language that also assimilated the natural world and sought to absorb its audience.